Some forts of Cracow Fortress become historical ruins. Purpose or necessity - Rojkowska-Tasak, Halina (Protection of Cultural Heritage, 2018)
Military objects of XIX century poligonal strongholds and from world war II period, similar to many industrial objects lost their primal function. Municipality of Cracow was given by the army, almost every fort from Cracow Fortress located within its boarder, including forts belonging to state, in different shape with adjacent ammunition shelters and eatrhworks. After unsuccessful leases City of Cracow decided to protect ruins of two forts from fortress’s northern section, located next to and cooperating with each other in the past – artillery fort No. 48 “Batowice” and armored fort No. 48a “Mistrzejowice”, which together with armored fort No. 47 ½ “Sudół” had formed one fortress group. Conservation projects of buildings protection, exposing their historical value and creating new elements which forms are corresponding with historical ones were developed for “Batowice” and “Mistrzejowice” forts. Realization of project in “Batowice” fort included: closing corridors in poterns with metal bars, closing all external openings with wooden doors (mainly in shelters) and renewing window bays with exposition of brick thread (only in three reconstructed bays) together with leaving small holes in the upper part of original windows protected with metal bars as a ventilation holes in barrack’s elevation. Fort “Mistrzejowice” is still waiting for project realization. Until now only conception of park with protected fort’s ruins was developed for “Sudół” fort. Also ruined earth bastions relicts in fort No. 2 “Kościuszko” are being discovered, with intention to convert them into park wherein will coexist earthen fortifcations and relicts of buildings excavated from the ground.